THE FIGHT AGAINST MONEY LAUNDERING IN THE CENTRAL AFRICAN SUBREGION CEMAC : STUDY IN THE LIGHT OF EUROPEAN AND INTERNATIONAL NORMS - (:unkn) unknown (My University, 2016)
Money laundering represents a real threat to the world economy. States are called upon to coordinate their efforts to effectively combat this scourge. That is why the States of the Economic and Monetary Community of Central Africa (CEMAC) have engaged in this struggle in the early 2000. They adopted an anti-money laundering institutional and normative framework which aims to reach the level of European and international standards in this area. The supranational normative texts adopted contain the incriminations and penal sanctions of the money laundering. Yet, the analysis of organic texts let not perceive any criminal jurisdiction vested in the CEMAC, its institutions or bodies. Moreover, the decision-making process leading to the adoption of these texts raised questions of legality and legitimacy. Also seeking the compliance of its anti-money laundering system to European and international norms, CEMAC has lost sight of its own regional realities so that the domestication of the approach to combating money laundering is then required for more efficiency.
Keywords: African Research